Integration of 21st Century Skills in Thematic Learning in Elementary School - Lailatul Alifah; Sukartono (Jurnal Ilmiah Sekolah Dasar, 2023)
The challenges of the 21st century require students to be responsive to advances in science and technology. Students need to prepare 21st century skills known as 4C (Critical Thinking, Communication, Collaborative, and Creativity). So that in learning there needs to be integration of 21st century skills combined with thematic learning. This study aims to analyse the integration of 21st century skills in thematic learning in elementary schools. This type of research uses a qualitative descriptive approach. The subjects of this study were teachers and third grade students. Data collection techniques are using observation, interviews, and documentation. Data validity technique used is triangulation. The data obtained will be analysed by reducing data, presenting data, and drawing conclusions. The results of the research on the integration of 21st century skills in thematic learning are shown through the activities carried out during learning. 21st century skills are integrated through discussion activities, solving problems that require high-order thinking skills, conveying arguments, and the ability to think with creative, innovative, and imaginative ideas. Through these learning activities, it can be concluded that the integration of 21st century skills in thematic learning is able to increase student activity in learning, increase potential, develop student skills, develop soft skill and hard skill competencies possessed by students in mastering thematic learning at school.